Диверсант: роман / Анатолий Азольский - Азольский Анатолий Алексеевич (Наш сериал, 2004)
Экземпляры: ЦБ (20210210) / Инвентарный номер: 41478 / Цена: 76.95 / Сис.шифр: Р2 / Авт.знак: А 35 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6